Methods for Solving Complex Problems in Fluids Engineering - Kang, Can.; Liu, Haixia; Zhang, Yongchao; Mao, Ning.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book describes recently developed research methods used to study complex problems in fluid engineering, especially optical flow measurement, flow visualization and numerical methods. It includes a wealth of diagrams and images, and the content is presented in a step-by-step manner from beginning to end, helping readers grasp the central points of the book. The book also presents a number of practical cases, illustrating how the research methods covered can be concretely implemented. Lastly, the book offers a valuable point of departure for pursuing further research.
Introduction to complex problems in fluid engineering -- A brief overview of research methods -- Submerged Waterjet -- Motion of Bubble -- Wake flow of the ventilation cylinder -- Drag-type hydraulic Rotor -- Viscous flows in the impeller pump -- Cavitation in the condensate pump -- Structural aspect of the impeller pump.
Keywords: Fluid mechanics; Thermodynamics; Computer-aided engineering; Mechanical engineering; Engineering Fluid Dynamics; Thermodynamics; Computer-Aided Engineering (CAD, CAE) and Design; Mechanical Engineering